AN EXAMINATION OF DIALECTICAL DEVIATION IN MALA KHALIL MSHAKHTI’S POEMS THROUGH GEOFFREY LEECH’S THEORY - Fatima Ali; Kamran Khalil (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ)
One of the basic characteristics of poetry, which makes difference between poetic language and daily spoken language, is deviation. Due to the fact that deviation plays a significant role in the language of a text, it has therefore been a subject of much debate among scholars and critics who have attempted to shed light on the importance of deviation on a text’s language and its types. Geoffrey Leech, a renowned linguist, has examined deviation thoroughly, unveiling its significance and types. According to Leech, a type of deviation is named as dialectical deviation in which the linguist oftentimes approaches the dialects of a language, and in this manner avoids the rules of the formal language. Mala Khalil Mshakhti is a Kurdish poet who places a significant reliance on dialectal deviation. It’s true that Mshakhti’s poetry is composed in the Kurdish Badini dialect, yet, the poet exhibits a special fondness for deviation in Kurdish Kurmanji and employs other dialects, too. Dialectical deviation in Mshakhti’s poetry doesn’t only employ a specific dialect but, in fact, includes a variety of Kurdish dialects. This deviation is so crucial that it’s regarded as an inevitable part of the poet’s style. This research focuses on the role and types of dialectical deviation in Mshakhti’s poetry, starting from the phonological aspect to the syntactic.